(3GdegPH aj aJGhi GdEeGe GdefUhQ HGddg YHO Gddg Hf MeRIs - (3eMeO Hf CSYO Hf YdGA Hf EHQGgje GdQGRis; (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s ((3eMeO Hf CSYO Hf RjO Hf CMeO GdePMLi s)
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf Ydi BdGFI GdeYJQajf HLejd HdGFg CeG HYO aEfi fXQJ ai eG LeYg eMji GdOjf eMeO Hf CMeO Hf Ydi Hf CMeO Hf GdhdjO GdbQTi GdUfYGfi Yf aJGhi CejQ GdeDefjf GdefUhQ HGddg ahLOJ eSGFd GdcJGH eTJHcI aQCjJ Cf CVe cd LfS Edis
(3BNQgG (B:s
(3hde jfcQ Pdc ef CMO ef GdUMGHI , hHg bVhG LejYkG hPdc eYdhe def Yde HGdCKGQ Je s
(3HgG fXGe GdJYbjHIs
(3HBNQgG eSGdI ai JcajQ GdeMjQI hCMcGege Ydi WQJgG Jedc HGSe MSf Hf eMeO Hf ehSi hhba efg Ydi HYVges
(3gPH Hg eG LeYg eMji GdOjf eMeO Hf CMeO Yf aJGhi GdEeGe s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs